IMUNITAS BUMN UNTUK MELAKUKAN MONOPOLI - Balvas Imantaka; Shandy Yudha Harswendo; Jopie Gilalo Jacous; Anisa Ilyanawati R. Yuniar (KARIMAH TAUHID, 2023)
ABSTRACT One of the prohibited practices is monopoly practice. Monopoly itself is the main componnent thaat will make wealth concentratd in the hands of a few group so that can create a social and economic inequality. Nevertheless, it turns out that State-Owned Enterprises can practice monopoly practices. The researrch method used is literature study that sourced from journals, articles until books and other scientific works so that what is written is not mere essays, but information that is valid or proven realistically. In addition, the sources used are Indonesian positive law or ius constitutum, namely the Law -Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. All issues in this study are included in Law Number 5 of 1999. ABSTRAK Salah satu praktek yang dilarang adalah praktek monopoli. Monopoli sendiri merupakan bagian utama yang dapat membuat kekayaan terpusat di tangan satu pelaku usaha sehingga berakibat kesenjangan sosial dan ekonomi. Kendati demikian, ternyata Badan Usaha Milik Negara dapat melakukan praktek monopoli. Metodologi yang digunakan adalah studi pustaka yang bersumber dari jurnal, artikel hingga buku dan karya ilmiah lainnya sehingga yang ditulis bukanlah karangan semata, melainkan informasi yang valid atau terbukti secara realistis.Selain itu, sumber yang digunakan adalah hukum positif Indonesia atau ius constitutum yaitu Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat. Semua persoalan dalam penelitian ini termakub dalam UU Nomor 5 Tahun 1999.